Nutritional value and antioxidant activity of ora-pro-nobis, tamarillo and green banana biomasses - Renata de Souza Ferreira; Jucenir dos Santos; Lívya Alves de Oliveira; Ceres Mattos Della Lucia; Márcia Cristina Teixeira Ribeiro Vidigal (The Journal of Engineering and Exact Sciences, 2024)
The consumption of unconventional food plants (UFP) can be a strategy to promote food and nutritional security, for which it is necessary to know their nutritional composition. The objective of this study was to analyze the nutritional value and antioxidant activity of ora-pro-nobis, tamarillo and bananas biomass (prata and nanica). Using standard methodologies (AOAC, 2005), the following compounds were analyzed in triplicate: protein, lipids, carbohydrate, calories, moisture, total fiber content, calcium, iron, vitamin C (by titrimetry), carotenoids (by High Performance Liquid Chromatography), phenolic compounds (by Folin-Ciocalteau) and antioxidant activities, by DPPH (2,2-diphenyl-1-picrylhydrazyl) and ABTS (2,2'-azino-bis 3-ethylbenzothiacholine-6-sulfonic acid). Ora-pro-nobis stands out as a source of calcium, iron, carotenoids and protein, is low in fat and has good antioxidant activity. Tamarillo showed high antioxidant activity, is a protein source and low in fat. The two banana biomasses had similar results in most nutrients, but the “nanica” banana with more protein and the “prata” with greater antioxidant activity. The unconventional food plants analyzed are potential bioactive foods, because they have phenolic compounds and high antioxidant activity. Thus, UFP have the potential to promote a more diverse and nutritious diet for consumers in general.